Heat Transfer Experiments on Electric Aircraft Battery Minichannels with Ethylene Glycol-Air Fluid - Marausna, Gaguk; A, Dhawysulthan M; Sitepu, Eric Leonardo; Kusuma, Muhamad Bayu Adi (Universitas Panca Marga, 2022)
The aviation industry has changed the mass and private transportation industry, thus making aircraft more and more varied, this type of air transportation has a very high adverse effect on the atmosphere because of its very high fuel consumption and emitting so many pollutants that aircraft for the future will lead There are 2 types of aircraft, namely Hybrid-Electric Aircraft and All-Electric Aircraft. Both have the same electric power drive, but there are weaknesses in this transportation. Namely on the battery used. In general, the battery used is Lithium-ion. Lithium-ion has the characteristics of being lightweight and more durable than the others. The battery itself also has a weakness, if it is used for too long or continuously the battery will heat up and reduce battery life. Therefore, cooling the battery is also needed to reduce battery heat and maintain battery life. The results obtained in this study are the use of working fluid 75% Ethylene Glycol –25% Water is better than 75% Water –25% Ethylene Glycol.